Diversification of the Public Budgets Incomes in Algeria - Rouag, Abdelwalid (Univerzita Pardubice, 2011)
This bachelor work deals with economies based on natural resource export and the heavy reliance of them public budgets on revenues from primer commodities such as oil and gas. It also describes the fiscal policies adopted by those countries to avoid them reliance from hydrocarbon revenues. The bachelor work contains also experiences provided by Norway and Algeria to make the former reliance less strong and make their economies more diversified.
Diverzifikace příjmů veřejných rozpočtů v Alžírsku
Keywords: ropa; přírodní zdroje; diverzifikace; fiskální politika; ropný fond; makroekonomická stabilita; lidský kapitál; veřejné investice; Alžírsko; Norsko; oil; resource curse; diversification; fiscal policy; oil fund; fiscal rules; macroeconomic stability; governance; human capital; public investments; Algeria; Norway